Structural Changes Induced by Heating in Sputtered NiO and Cr2O3 Thin Films as p-Type Transparent Conductive Electrodes - Cecilia Guillén; José Herrero (Electronic Materials, 2021)
NiO and Cr2O3 are transition metal oxides with a partially filled d electron band that supports p-type conduction. Both are transparent to the visible light due to optical absorption beginning at wavelengths below 0.4 μm and the creation of holes by metal vacancy defects. The defect and strain effects on the electronic characteristics of these materials need to be established. For this purpose, NiO and Cr2O3 thin films were deposited on unheated glass substrates by reactive DC sputtering from metallic targets. Their structural, morphological, optical and electrical properties were analyzed comparatively in the as-grown conditions (25 °C) and after heating in air at 300 °C or 500 °C. The cubic NiO structure was identified with some tensile strain in the as-grown conditions and compressive strain after heating. Otherwise, the chromium oxide layers were amorphous as grown at 25 °C and crystallized into hexagonal Cr2O3 at 300 °C or above also with compressive strain after heating. Both materials achieved the highest visible transmittance (72%) and analogous electrical conductivity (~10−4 S/cm) by annealing at 500 °C. The as-grown NiO films showed a higher conductivity (2.5 × 10−2 S/cm) but lower transmittance (34%), which were related to more defects causing tensile strain in these samples.